2012
DOI: 10.1039/c1nr11443c
|View full text |Cite
|
Sign up to set email alerts
|

A methodology for preparing nanostructured biomolecular interfaces with high enzymatic activity

Abstract: The development of a novel method for functionalizing nanopatterned surfaces with catalytically active proteins is reported. This method involves using dip-pen nanolithography (DPN) and polymer pen lithography (PPL) to generate nanoscale patterns of coenzyme A, followed by a phosphopantetheinyl transferase-mediated coupling between coenzyme A and proteins fused to the ybbR-tag. By exploiting the ability to generate protein features over large areas afforded by DPN and PPL, it was now possible to measure protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 47 publications
(56 reference statements)
0
22
0
Order By: Relevance
“…Therefore, one can fabricate molecular patterns spanning from ∼100 nm to many micrometers over large areas rapidly. Indeed, it has been demonstrated that PPL is capable of fabricating multi‐scale molecular patterns for making electronic circuits, metal and semiconductor nanoparticle arrays, DNA arrays, and multiplexed protein arrays 21, 23, 27–31…”
mentioning
confidence: 99%
“…Therefore, one can fabricate molecular patterns spanning from ∼100 nm to many micrometers over large areas rapidly. Indeed, it has been demonstrated that PPL is capable of fabricating multi‐scale molecular patterns for making electronic circuits, metal and semiconductor nanoparticle arrays, DNA arrays, and multiplexed protein arrays 21, 23, 27–31…”
mentioning
confidence: 99%
“…53 Such genetic recombinant methods could be utilised to generate and select enzymes specically for cSPL applications. Biocatalytic cSPL would also benet from harnessing improved site-specic enzyme immobilisation methods, 54,55 to ensure that the enzymes attached to the probes retain maximum activity. This aspect is particularly crucial for nanoscale applications where relatively few protein molecules can be located on a single nanoscale object.…”
Section: Discussionmentioning
confidence: 99%
“…[36] Distinguished from other peptide-tag based protein labeling techniques, the Bs_Sfp-catalyzed chemical labeling of 4'-phosphopantetheinylation showed impressive tolerance to accommodate various CoA analog substrates. Structurally different CoA analogs were synthesized by conjugation with quantum dot (QD), [37] poly(ethylene glycol) (PEG) polymer brush, [38] nanofabricated surface, [39] polystyrene nanoparticle, [40] oligopeptide [41] (Figure 2D, LPETGGÀ CoA) and cytotoxic payload [42] (Figure 2D, auristatinÀ CoA). These derivatives have been applied for cell-surface protein imaging, protein immobilization, enzyme evolution as well as preparation of antibody-drug conjugates (ADCs).…”
Section: Pptase-catalyzed Chemical Labeling Of 4'-phosphopantetheinylmentioning
confidence: 99%